Feast or famine : evidence for mixed capital–income breeding strategies in Weddell seals - K Wheatley; C Bradshaw; R Harcourt; M Hindell (2008)
Evolved patterns of resource expenditure for reproduction have resulted in a life history continuum across species. A strictly capital-breeding strategy relies extensively on stored energy for reproduction, whereas income breeding uses energy acquired throughout the reproductive period. However, facultative income breeding has been shown in some classically capital-breeding animals, and was originally thought to provide a nutritional refuge for smaller females incapable of securing sufficient reserves during pre-partum foraging. We examined milk composition and milk output for the Weddell seal to determine to what degree lactation was aided by food intake, and what factors contributed to its manifestation. Milk composition was independent of maternal post-partum mass and condition, but did change over lactation. Changes were most likely in response to energetic and nutritional demands of the pup at different stages of development. During early lactation, females fasted and devoted 54.9% of total energy loss to milk production. Later in lactation 30.5% more energy was devoted to milk production and evidence suggested that larger females fed more during lactation than smaller females. It appears that Weddell seals may exhibit a flexible strategy to adjust reproductive investment to local resource levels by taking advantage of periods when prey are occasionally abundant, although it is restricted to larger females possessing the physiological capacity to dive for longer and exploit different resources during lactation. This supports the assumption that although body mass and phylogenetic history explain most of the variation in lactation patterns (20–69%), the remaining variation has likely resulted from physiological adaptations to local environmental conditions. Our study confirms that Weddell seals use a mixed capital–income breeding strategy, and that considerable intraspecific variation exists. Questions remain as to the amount of energy gain derived from the income strategy, and the consequences for pup ...